ANALISIS PENGHAMBAT REVITALISASI PASAR DALAM MENJAGA EKSISTENSI PASAR TRADISIONAL PADANGSIDIMPUAN - Mufti Fahrizal Harahap (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2024)
The revitalization of the Padangsidimpuan traditional market which has been carried out by the Padangsidimpuan City Government is not only by completely overhauling the physical market building but also making innovations such as 1) Implementing digital money 2) Creating memberships for buyers, 3) Launching a Digital Market Pilot, and 4) creating a traditional market Padangsidimpuan city as a tourist market. Through research using a qualitative approach, the results obtained were that in its implementation, the traditional market revitalization program was faced with several inhibiting factors, namely: The existence of resistance from market traders, and market management problems including the concept of arranging sales places that did not make it easy for sellers and buyers, locations that were less strategic because they were not there is no public transportation, a small parking area, and the absence of capital from traders who used to be in the market for a long time before therevitalization and relocation.